Perlindungan Hukum Para Anggota Koperasi Menjalankan Kegiatan Usaha Sektor Jasa Keuangan - Louis Budiyanto Limowandoho (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
The promulgation of Law no. 4 of 2023 concerning Development and Strengthening of the Financial Sector (UUPPSK) for joint business activities (cooperatives) in the financial services sector, does not revoke Law no. 25 of 1992 concerning Cooperatives (Cooperative Law). Providing cooperative members with the choice of running pure cooperative business activities (from members to members/close loop) or open cooperatives (open loop/collecting funds outside members as well as distributing funds to non-members, supervision and participation of the Financial Services Authority (OJK). Occurs the mixing of cooperative capital and double supervision by the Cooperative Supervisory Board and supervision from the Financial Services Authority (OJK). The issue of whether cooperatives (close loop) and cooperatives (open loop) guarantee legal certainty and whether double supervision of cooperative business activities provides legal protection to cooperative members. . The method used in this research is normative juridical with a statutory regulation approach and a conceptual approach. The following research results were obtained: Cooperatives that run service businesses in the financial sector are regulated by the Cooperative Law and UUPPKS, mixing internal and external member capital, double supervision. , making there no legal certainty, because positive law is legislation, it cannot be easily changed, so that there is legal certainty. Collecting and distributing cooperative capital to non-members in case of default does not provide legal protection to members, because savings, whether mandatory, principal or voluntary, are not guaranteed by the Deposit Insurance Corporation. Keywords: Legal Protection; Cooperative Members; Financial Services Sector.